Leaching Behavior of a Salinized Field in the Lower Reaches of the Syr-Darya River, Kazakhstan - Sokei, Yoshimi; Wasano, Kikuo (Annals of Arid Zone, 2016)
In the lower reaches of the Syr-Darya River vast land areas have become wet deserts because of salinity problem as a consequence of rice-based cropping system. To investigate the reclamation strategy for such areas, one field was leached twice and cultivation trials, using furrow irrigation; were conducted after the leaching. The salinity (ECe) of 0 to 20 cm surface soil was decreased by leaching from 71.2 to 7.9 dS m-I. The groundwater level during trial was at I to 2 m depth. The ECgw values in the studied area varied from 3.2 to 87.9 dS m-l , and were almost constant regardless of the irrigation for cultivation. The mean ECe value at 20 to 25 cm depth in the trial field after cultivation was 6.0, dS m-l, while values in non-leached arable and abandoned field's were 12.7 and 50.0 dS m-I, respectively. The values increased with decreasing soil depth. In the trial field, correlation coefficients between the clay content and ECe values were high at the same depth at 0.77* at 20 to 25 cm and at 0.87* at 60 to 65 cm. In the non-leached fields. correlation coefficients between the clay content at 90 to 95 cm depth and ECe values at each depth studied (20-25, 60-65 and 90-95 cm) were high. These results showed that (I) leaching was effective in reclaiming fields in this area, (2) upland crop-based furrow irrigated agriculture can replace rice-based rotation, and (3) installing subsurface drainage systems at approximately 100 cm depth is required ..